Image Reconstruction from Sparse Samples Using Directional Total Variation Minimization - Demircan Türeyen, Ezgi; Kamasak, Mustafa E.; Bayram, İlker (IEEE, 345 E 47Th St, New York, Ny 10017 USA, 2016)
This paper considers reconstruction of missing pixels and formulates the problem under directional total variation (DTV) regularization. In order to devise an algorithm, forward-backward splitting method is used as a convex optimization tool, in conjunction with a fast projected gradient-based algorithm. The results are compared with the results of TV-based setting, and the utility of using DTV is shown in terms of accuracy, when an image with a dominant direction is the case.
Keywords: image reconstruction; directional total variation; convex optimization; proximal splitting methods; Algorithms